Association Between Use of Prophylactic Indomethacin and the Risk for Bronchopulmonary Dysplasia in Extremely Preterm Infants - Jensen, Erik A. (J Pediatr, 2017)
OBJECTIVE: To assess the association between prophylactic indomethacin and bronchopulmonary dysplasia (BPD) in a recent, large cohort of extremely preterm infants. STUDY DESIGN: Retrospective cohort study using prospectively collected data for infants with gestational ages < 29 weeks or birth weights of 401–1000g born between 2008 and 2012 at participating hospitals of the National Institute of Child Health and Human Development Neonatal Research Network. Infants treated with indomethacin in the first 24 hours of life were compared with those who were not. Study outcomes were BPD, defined as use of supplemental oxygen at 36 weeks postmenstrual age among survivors to that time point, death, and the composite of death or BPD. Pre-specified subgroup analyses were performed. RESULTS: Prophylactic indomethacin use varied by hospital. Treatment of a patent ductus arteriosus (PDA) after the first day of life was less common among 2,587 infants who received prophylactic indomethacin compared with 5,244 who did not (21.0% vs. 36.1%, p<0.001). After adjustment for potential confounders, use of prophylactic indomethacin was not associated with higher or lower odds of BPD (OR 0.89, 95% CI 0.72–1.10), death (OR 0.80, 95% CI 0.64–1.01), or death or BPD (OR 0.87, 95% CI 0.72–1.05). The only evidence of subgroup effects associated with prophylactic indomethacin were lower odds of death among infants with birth weights above the 10(th) percentile and those who were not treated for a PDA after the first day of life. CONCLUSIONS: Prophylactic indomethacin was not associated with either reduced or increased risk for BPD or death.